Pelatihan Penyusunan Buku Ajar Berbasis Problem-Based Learningdengan Bantuan Artificial Intelligence di SMK - Nurhadi, Nurhadi; Hermawan, Hermawan (Presisi: Jurnal Pengabdian Masyarakat, 2025)
This research aims to improve teachers' pedagogical competence and digital literacy through training in the preparation of Problem-Based Learning (PBL)-based textbooks with the support of Artificial Intelligence (AI) at SMK Ar-Raisiyah Husada Jakarta. The research background is based on the urgent need for vocational learning innovation in the era of Industrial Revolution 4.0 and Society 5.0, where teachers are required not only to master technical content, but also to be able to design creative, collaborative, and contextual learning. This study uses a qualitative approach with case study design through practice-based training (workshops), intensive mentoring, and thematic analysis of observational data, interviews, questionnaires, and documentation. The results of the study show that PBL-AI-based training has succeeded in improving teachers' ability to design problem-based learning scenarios, strengthening digital literacy through the use of generative AI tools, and encouraging a paradigm shift in teaching from teacher-centered to student-centered. In addition, this activity produced concrete products in the form of AI-assisted contextual pharmacy textbook prototypes that are suitable for use in vocational learning. Conceptually, this research contributes to the development of a practice- based teacher training model that integrates AI and PBL as a 21st century competency strengthening strategy. These findings also provide practical implications for vocational teacher capacity building policies towards an adaptive, reflective, and future-oriented digital education transformation.